PERLINDUNGAN HUKUM TERHADAP PEMENANG LELANG TERKAIT KEPEMILIKAN TANAH SECARA ABSENTEE AKIBAT PEMINDAHAN HAK ATAS TANAH KARENA LELANG OBJEK HAK TANGGUNGAN - Ayu Purnama Dewi, Ni Kadek; Ari Yuliartini Griadhi, Ni Made (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 05, Oktober 2014)
This scientific work titled Against Legal Protection If the Winning BidderHappened In Absentee Ownership of Land Transfer of Land Rights Due for ObjectAuction Mortgage. The background of this paper is the result of absentee landownership transfer of land rights as the auction is not to be adverse legal subjectsoutside the district, the winner of the auction. The purpose of this paper is to understandthe legal protection of absentee land ownership as a result of the transfer of land rightsas the auction object security rights. This paper uses the normative method by analyzingthe problems with the law and relevant literature. The conclusion of this paper is thelegal protection of the relevant auction winner absentee land ownership as a result ofthe transfer of land rights as the auction object security rights are contained in Article 3of Government Regulation Number 224 of 1961 in paragraph (5) and GovernmentRegulation Number 224 of 1961 and Government Regulation Number 41 Year 1964 onImplementation of Land Distribution and indemnity Provision.
Keywords: Protection of Law, Auctions Mortgage, Land of the Absentee, and Object Mortgage